God, an Event of Proximity, Narrated in Luke 10:25–37 - Diego Fernando Bedoya Bonilla (Collectanea Theologica, 2022)
The so-called “phenomenological turn” proposes a return to the world of lived experience, overcoming the rigidity of classical ontology. In this sense, theology also proposes to speak of God migrating from the world of the concept to life itself. Keeping in mind, then, that God gives himself in history as a Mystery of infinite love, it is necessary to find a new category that can express him, being faithful to the biblical testimony. The category chosen is “event,” as proposed by Claude Romano, who understands the event (happening) as the irruption of the unexpected that significantly affects everything that comes into contact with it. The parable of the Samaritan (Luke 10:25–37) reveals God as an event of loving proximity, who mercifully bursts in through the actions of a Samaritan who saves the life of a seriously wounded man. The confirmation of the possibility of using the category “event” to speak of God is given only by means of a narrative method, for which we make use of the hermeneutical contributions of A. Wénin, who makes narrative the most appropriate language to express God’s traits, in this case, his merciful closeness.